Successive loadings of reactant in the hydrogen generation by hydrolysis of sodium borohydride in batch reactors - M. J. F. Ferreira (2009)
In this paper, for the first time, an experimental investigation is presented of five successive loadings of reactant alkaline solution of sodium borohydride (NaBH4) for hydrogen generation, using an improved nickel-based powder catalyst, under uncontrolled ambient conditions. The experiments were performed in two batch reactors with internal volumes of 0.646 l and of 0.369 l. The compressed hydrogen generated, at pressures below hydrogen critical pressure, gives emphasis on the importance of considering solubility effects during reaction, leading to storage of hydrogen in the liquid phase inside the reactor. The present work suggests that the sodium metaborate by-product formed by the alkaline hydrolysis of NaBH4, in a closed pressure vessel without temperature control, is NaBO2.xH2O, with x ≥ 2. The data obtained in this work lends credit to x ≈ 2, which was discussed based on the XRD results, and this call for increased caution in the definition of the hydrolysis reaction of NaBH4 up to temperatures of 333 K and up to pressures of 0.13 MPa